2021
DOI: 10.1111/1744-7917.12972
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of glucose transporter 4 in ovarian development and reproductive maturation of Harmonia axyridis (Coleoptera: Coccinellidae)

Abstract: Glucose is vital to embryogenesis, as are glucose transporters. Glucose transporter 4 (Glut4) is one of the glucose transporters, which is involved in rapid uptake of glucose by various cells and promotes glucose homeostasis. Although energy metabolism in insect reproduction is well known, the molecular mechanism of Glut4 in insect reproduction is poorly understood. We suspect that Glut4 is involved in maintaining glucose concentrations in the ovaries and affecting vitellogenesis, which is critical for subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…As stated before, RNAi‐mediated silencing has been applied to agricultural pests and human disease vectors, but few studies have focused on the functional genomics of natural enemies, such as predators and parasitoids (Castellanos et al, 2022; Yan et al, 2023). Most related work on predators is related to ladybird beetles, such as H. axyridis (Han, Han, et al, 2022; Li et al, 2022; Tian et al, 2022; Tsuji et al, 2018)a. Furthermore, studies on the potential effects of pest‐designed RNAi on nontarget organisms are scarce, with only a few involving ladybird beetles.…”
Section: Discussionmentioning
confidence: 99%
“…As stated before, RNAi‐mediated silencing has been applied to agricultural pests and human disease vectors, but few studies have focused on the functional genomics of natural enemies, such as predators and parasitoids (Castellanos et al, 2022; Yan et al, 2023). Most related work on predators is related to ladybird beetles, such as H. axyridis (Han, Han, et al, 2022; Li et al, 2022; Tian et al, 2022; Tsuji et al, 2018)a. Furthermore, studies on the potential effects of pest‐designed RNAi on nontarget organisms are scarce, with only a few involving ladybird beetles.…”
Section: Discussionmentioning
confidence: 99%
“…were hydrolyzed to supplement this [ 55 , 56 ]. Glucose levels were elevated in mutant female adults; the reason for this may be that female mutants need energy to maintain normal life activities, such as mating and spawning [ 57 ]. Studies have shown that many insects need to use proteins and carbohydrates to synthesize sufficient lipids; as a result, insects can reach sexual maturity and lay eggs [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%